Effect of Preoperative Intravitreal Bevacizumab on the Success of Trabeculectomy with Mitomycin C in Neovascular Glaucoma - Fuad Ahmad Khan Niazi , Muhammad Imran Janjua , Muhammad Rizwan Khan ,Muhammad Afzal Khan Niazi, (Journal of Rawalpindi Medical College, 2015)
Background: To assess the effect of preoperative Intravitreal Bevacizumab on the success of Trabeculectomy with Mitomycin C in neovascular glaucoma. Methods: In this case control study 21 eyes of 21 patients with neovascular glaucoma irrespective of the primary pathology were selected. All of them were given Intravitreal Bevacizumab one to two weeks prior to a conventional primary trabeculectomy with Mitomycin C. All eyes were then followed after 01 month for the surgical outcome of success, which was an IOP of less than 21 mmHg without medication with a functioning bleb. Intravitreal Bevacizumab was given in a dose of 1.25mg/.05ml using a 29 gauge insulin syringe , approximately one to two weeks prior to a planned primary trabeculectomy.The trabeculectomy procedures were all performed under local anesthesia (facial and peribulbar block). A fornix based conjunctival flap was lifted and a 4mm x 2mm rectangular sclera flap raised and Mitomycin C, in a concentration of 0.5mg/ml applied beneath the scleral and conjunctival flaps using a soaked sponge for 4 to 5 minutes and later washed with 20 ml Ringer’s Lactate solution. A sclerotomy was then fashioned measuring 1.5mm x 1mm and a peripheral iridectomy performed. The scleral flap was sutured back using two 10/0 nylon stitches at the two corners. The conjunctival flap was also then sutured with 10/0 nylon. All the patients were followed up regularly and their IOP assessed at 01 month. The mean IOP was then calculated for all the patients as a measure of success of following this treatment protocol. Results: Majority (61.9%) were females. Mean age at presentation was 52.6 +8.7 years. Mean preoperative IOP was 37.2 +8.8 mmHg and mean postoperative IOP at one month was 15.2 +3.7 mmHg. There was no or minimal hemorrhage peroperatively. Hypotony was seen in 25%.